Surveying neotropical social wasps. An evaluation of methods in the "Ferreira Penna" research station (ECFPn), in Caxiuanã, PA, Brazil (Hym, Vespidae, Polistinae) - Silveira, Orlando Tobias (Papéis Avulsos de Zoologia, 2002)
.